APLIKASI EDIBLE COATING MINYAK KAYU MANIS PADA MANISAN TOMAT CHERRY SELAMA PENYIMPANAN - Priska Wisudawaty; Indah Yuliasih; Liesbetini Haditjaroko (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Candied cherry tomatoes with antimicrobial edible coatings are one of the alternative product processing technologies that can be developed to maintain the quality and extend shelf life. This study aimed to analyse the effect of antimicrobial edible coating on the cherry tomato quality changes during storage. The experimental design in this study used Completely Randomized Design consists of one factor, namely edible coating which performed twice as replication. The level of treatment test was candied cherry tomatoes without an edible coating, with an edible coating without antimicrobial, and with an antimicrobial edible coating. Based on the analysis of water content, total sugar, total acid, vitamin C, total microbe, hardness, and pH, candied cherry tomato with an antimicrobial edible coating was the best treatment. The rate of change water content, total sugar, total acid, vitamin C, total microbial, hardness, and pH of the product respectively, were 0.1436, 0.3002, 0.0058, 0.0048, 690.8838, 0.0378, 0.0163, 10.94, and 30.07 %, respectively. The results of organoleptic tests on aroma, taste, color, and texture showed that 25.71, 15.71, 65.71, and 55.71%, respectively, of panelists who like candied cherry tomatoes with antimicrobial edible coatings. Keywords: antimicrobial, candied cherry tomato, cinnamon oil, edible coating